Rodas de conversa na educação infantil: desafios e possibilidades para uma educação dialógica - Rossetto, Carolina (2016)
The research presented here suggests a conversation around the dialogue and its role in the affirmation of children as subjects of law, desire and knowledge. The statement of a pedagogy for early childhood education grounded in dialogical communication can bring out an educational work outlined in cooperation, autonomy, affectivity, the possibility of being, that, exceeding the sphere of merely recognized rights, will vinculá- it a political act, as desirable activity. In this sense, the conversation wheel is referred to and discussed as a pedagogical device that can contribute to the educational work. The conversation wheel activity is an ongoing activity, the issues circulating in the wheel of time are precious help in the organization of work, the interest of students to study any subject more criteria, raising hypotheses, their experiences outside the environment school, conflicts with friends, the grief of losing a loved one, separation from parents, the arrival of a little brother, finally, the context of the themes of their realities. The timing of the wheel takes place collectively, so the child feels more at ease, because the language expressed in this wheel is a language of her age, she hears his friend saying they often also feel like saying and can only after a start it, or it can be a motivator for your friends. The wheel they learn that does not resolve things hitting but talking. If we solve things talking, then it is through dialogue that we will learn new and interesting things, it is through dialogue that we exercise our kindness, our care for each other, and through dialogue walked to a dialogic education, where no one is better anyone where together we learn best